2019
DOI: 10.3390/app9204370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water-Soaking Height on the Deformation and Failure of Coal in Uniaxial Compression

Abstract: The stability of water-preventing coal pillar plays an important role in preventing gob water inrush. The gob side of the water-preventing coal pillar is soaked in a certain height of mine water. Different soaking heights may affect the stability of coal pillars. Few studies have been conducted on the properties of coals with different water-soaking heights. We carried out uniaxial compressive tests on coal specimens with different water-soaking heights to gain a better understanding of different water-soaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The results show that temperature changes the intensity of the water-rock interactions. Qian et al [8] performed uniaxial compressive tests on coal specimens with different water-soaking heights to gain an improved understanding of different water-soaking height-induced weakening characteristics of coal. The results show that the AE activities of complete water-soaking and non-soaking coal specimens are relatively concentrated, occurring mainly in the unstable fracture expansion and post-peak destruction stages, and AE exhibits a main-shock mode.…”
Section: State Of the Artmentioning
confidence: 99%
“…The results show that temperature changes the intensity of the water-rock interactions. Qian et al [8] performed uniaxial compressive tests on coal specimens with different water-soaking heights to gain an improved understanding of different water-soaking height-induced weakening characteristics of coal. The results show that the AE activities of complete water-soaking and non-soaking coal specimens are relatively concentrated, occurring mainly in the unstable fracture expansion and post-peak destruction stages, and AE exhibits a main-shock mode.…”
Section: State Of the Artmentioning
confidence: 99%
“…For soft coal, as the water saturation increases, the uniaxial compressive strength first increases and then decreases (Gu et al 2019). For ordinary rocks and hard coal, water generally only leads to strength reduction (Feng et al 2019;Qian et al 2019) because the water-rock interaction reduces rock cohesion (Guo et al 2018;, degrades fracture toughness, and promotes subcritical crack propagation (Hao et al 2015;Ma et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This process concluded that the weakening of the peak stress and strength, elastic, strain, and the post-peak Energies 2021, 14, 3103 2 of 13 modulus decreased to some extent with increasing moisture content and loading rate. To understand the weakening characteristics of coal induced by different water content levels, Qian et al [17] tested coal samples with different water contents and found that the acoustic emission phenomenon was relatively obvious for fully saturated and non-saturated coal specimens. In the process of exploring the main factors affecting water-rock interaction, Heggheim et al [18] analyzed the softening behavior of sandstone by analyzing the sandstone grain variation, pore morphology and pore size.…”
Section: Introductionmentioning
confidence: 99%